Creutzfeldt-Jakob disease in the elderly. Issue 863 (September 1997) - de Silva, R.; Findlay, C.; Awad, I.; Harries-Jones, R.; Knight, R.; Will, R.
Abstract : Creutzfeldt-Jakob disease (CJD) is typically described as a pre-senile dementia. However, cases do occur in the elderly and a case of sporadic CJD in an 86-year-old patient is described. The database of the UK national surveillance unit has been studied, and the age-specific incidences for various age groups over the period 1980-93 calculated. Cases of CJD in those over 80 years old have been identified and their clinical characteristics examined. There is no evidence that CJD presents atypically in the elderly, or that large numbers of cases are being missed in the elderly due to poor ascertainment.